The Role of Arbuscular Mycorrhizal Fungi Density and Diversity on the Growth and Biomass of Corn and Sorghum Forage in Trapping Culture - M. Husein; N. Umami; A. Pertiwiningrum; M. M. Rahman; D. Ananta (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aimed to determine the effectiveness of arbuscular mycorrhizal fungi (AMF) in the absorption of nutrients in trapping culture and its effects on the growth and biomass production of corn (Zea mays L.) and sorghum (Sorghum sp.). Soil samples with rhizosphere were collected from three different places: Bambusa sp., Cichorium intybus L., and Pinus merkusii. The density and genus of AMF spores were evaluated. AMF effectiveness was tested using six levels of rhizosphere and two species (corn and sorghum) of plants with a 2×6 factorial experiment with eight replications of each treatment. Six types of rhizospheres were: (i) bamboo rhizosphere (Bambusa sp.) (T1), (ii) control for T1 (C1), (iii) chicory rhizosphere (C. intybus L.) (T2), (iv) control for T2 (C2), (v) Pine rhizosphere (P. merkusii) (T3), and (vi) control for T3 (C3). The control treatment was derived from sterilized planting media. The results showed that the root rhizosphere of Bambusa sp. had more density and diversity of AMF spores than the root rhizosphere of C. intybus L. and P. merkusii. At the end of the trapping culture, the host plants sorghum and corn increased the density of spores in the carrier medium or propagules of the three rhizosphere types. The difference in the amount of initial AMF had a significant (p<0.05) effect on plant height, the number of leaves, and the biomass production of trapping plants. It can be concluded that more density and colonization of arbuscular mycorrhizal spores show higher growth and biomass of trapping plants.